Equilibrium in the symmetric Hirshleifer contest: Uniqueness and characterization - Christian Ewerhart; Guang-Zhen Sun (University of Zurich, Department of Economics, 2018)
The symmetric two-player Hirshleifer (1989) contest is shown to admit a unique equilibrium. The support of the equilibrium strategy is finite and includes, in particular, the zero expenditure level. We also establish a lower bound for the cardinality of the support and an upper bound for the undissipated rent.
Keywords: C72; D72; D74; 330; Contests; mixed-strategy equilibrium; rent dissipation; uniqueness